2011
DOI: 10.1093/cid/cir244
|View full text |Cite
|
Sign up to set email alerts
|

Men Who Have Sex With Men, Risk Behavior, and HIV Infection: Integrative Analysis of Clinical, Epidemiological, and Laboratory Databases

Abstract: Together, our findings suggest that the sexual behavior of MSM, both HIV-infected and uninfected, has become riskier, contributing to the number of those seeking early clarification of status, to syphilis comorbidity, and to the spread of drug resistance. These findings call for action by public health planners and community-based organizations aimed at increasing awareness of the risks, bringing a change in attitude and establishing safe sex norms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 24 publications
4
43
0
Order By: Relevance
“…The annual number of newly diagnosed HIV/AIDS infections among MSM in Israel has tripled during the past decade 3. STI rates among MSM in Israel are also disproportionately higher than recorded in heterosexual men,4 similar to reports from other developed countries 5–7…”
mentioning
confidence: 67%
“…The annual number of newly diagnosed HIV/AIDS infections among MSM in Israel has tripled during the past decade 3. STI rates among MSM in Israel are also disproportionately higher than recorded in heterosexual men,4 similar to reports from other developed countries 5–7…”
mentioning
confidence: 67%
“…15 In accordance with a previous study reporting a trend towards an increase in syphilis incidence rates among HIV-infected MSM, this study had similar results. 16 Several STDs have also been reported to be risk factors for HIV transmission. 17e19 A previous study in Taiwan that enrolled VCT clients also found that clients with at least one STD other than HIV had a significantly higher prevalence of HIV infection than those without any The study and reference sequences were aligned by the Clustal W program with minor manual adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…The number of MSM newly diagnosed with HIV has tripled in Israel during the last decade, as well as their proportion of all new men reported annually with HIV/AIDS 2. Likewise, MSM presented higher rates of sexually transmitted infections (STI) than heterosexuals in the walk-in STI clinic in Tel Aviv,3 as has been reported from other industrialised countries 4 5…”
Section: Introductionmentioning
confidence: 94%